The Dynamic History of the Journey of Pancasila as the Foundation of the Indonesian State - I Gusti Ngurah Santika; I Made Kartika; I Gede Sujana; Ni Made Adhi Dwindayani (Journal of Sustainable Development Science, 2023)
The fundamental weakness in Pancasila education is the lack of discussion about the history of the dynamics of the journey of Pancasila in Indonesia. This research aims to find out the history of the dynamics of the journey of Pancasila as the basis of the Indonesian state. The method used in this research is descriptive qualitative. The method of data collection in the study uses literature studies or literature. The results of this study show that during the independence revolution, Pancasila as the basis of the state only applies in one state, so it has not played a functional role. In the RIS Constitution, there are differences in the values of Pancasila contained in the 1945 Constitution. During the time the Old Order was in power, Pancasila was not implemented, but was distorted through its actions. In the New Order era, Pancasila was manipulated with various interpretations to cover up its deviant policies. In the reform era, Pancasila was submerged by the dynamics or hustle and bustle of political development and democracy in Indonesia. Pancasila began to be forgotten and abandoned by its supporters